What are the priorities of bureaucrats? Evidence from conjoint experiments with procurement officials - Tukiainen, Janne; Blesse, Sebastian; Bohne, Albrecht; Giuffrida, Leonardo M.; Jaaskelainen, Jan; Luukinen, Ari; Sieppi, Antti (Elsevier, 2025)
While effective bureaucracy is crucial for state capacity, its decision-making remains a black box. We elicit preferences of 900+ real-world public procurement officials in Finland and Germany. This is an important pursuit as they report having sizeable discretion and minimal extrinsic incentives. Through conjoint experiments, we identify the relative importance of multiple features of procurement outcomes. Officials prioritize avoiding unexpectedly high prices over seeking low prices. Avoiding winners with prior bad performance is the most important feature. Officials avoid very low competition, while litigation risks and regional favoritism matter less. Preferences and office interests appear well-aligned among bureaucrats.